Estudio del artefacto vestimentario: la faja del pueblo Saraguro - Chuqui Lanchimba, Katerin Michel (2024)
The present project seeks to visualize the importance, the dimensions of use, symbolic, communicative and technically productive of the Saraguro woman's girdle, giving greater emphasis to the clothing artifact beyond the practical day-to-day function, seeking to know why young adolescents They have stopped using the girdle compared to adult women who wear this accessory every day. The sash is an important accessory with cultural richness, it can be analyzed from fashion and its methodology is a mixed approach because the natives of the area were included, specifically the artisans and women. In such a way that results have been obtained based on semi-structured and triangulated interviews, as well as bibliographic files, observation sheets of the functions of the clothing artifact. As a result of the analysis of the practical, symbolic communicative, technical productive functions and interviews, it was possible to identify a new practical function which is the protection of the navel considered as a central part of the human being, and it is verified that adolescent women do use the girdle, but less frequently compared to the more adult population. Likewise, a comparison was made between the current sashes and the old sashes, determining changes in the width of the sash and graphic motifs, symbology, use of dark colors to light colors